2020
DOI: 10.1523/jneurosci.1907-20.2020
|View full text |Cite
|
Sign up to set email alerts
|

Reelin-Nrp1 Interaction Regulates Neocortical Dendrite Development in a Context-Specific Manner

Abstract: Reelin plays versatile roles in neocortical development. The C-terminal region (CTR) of Reelin is required for the correct formation of the superficial structure of the neocortex; however, the mechanisms by which this position-specific effect occurs remain largely unknown. In this study, we demonstrate that Reelin with an intact CTR binds to neuropilin-1 (Nrp1), a transmembrane protein.Both male and female mice were used. Nrp1 is localized with very-low-density lipoprotein receptor (VLDLR), a canonical Reelin … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
14
0

Year Published

2021
2021
2025
2025

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 22 publications
(15 citation statements)
references
References 78 publications
(117 reference statements)
1
14
0
Order By: Relevance
“…While the CTR is likely flexible due to its disproportionately basic composition, structural predictions suggest that the CTR is not completely disordered but does have secondary/tertiary structure. This fits with the current understanding of the CTR, as it has increasingly been shown to serve as a multifunctional domain that not only affects Reelin's secretion and signaling levels but also interacts with the recently reported Reelin binding partner, NRP-1 (26,28,37).…”
Section: Discussionsupporting
confidence: 86%
See 3 more Smart Citations
“…While the CTR is likely flexible due to its disproportionately basic composition, structural predictions suggest that the CTR is not completely disordered but does have secondary/tertiary structure. This fits with the current understanding of the CTR, as it has increasingly been shown to serve as a multifunctional domain that not only affects Reelin's secretion and signaling levels but also interacts with the recently reported Reelin binding partner, NRP-1 (26,28,37).…”
Section: Discussionsupporting
confidence: 86%
“…RR8 has been of increasing interest to those in the Reelin field, as new developments in its function and regulation have been reported, especially regarding the CTR (26,28,37). Despite not being able to represent the CTR in our crystallographic model of RR8, we confidently identify the region that the CTR occupies using SAXS.…”
Section: Discussionmentioning
confidence: 93%
See 2 more Smart Citations
“…The substitution of a negatively charged amino acid with a neutral one could have an impact on the folding of RELN, thus preventing the protein to acquire the proper conformation to be correctly cleaved or to bind to its receptors (VLDLR and ApoER2). A recent study ( 60 ) described a similar phenotype after overexpression of RELN in a Nrp1 knockdown (KD) mouse model. The authors demonstrated that Nrp1 forms a complex with VLDLR to which RELN strongly binds and its knocked-down results in a misorientation of electroporated cells in the aggregates.…”
Section: Discussionmentioning
confidence: 84%